SEASONAL VARIATION IN MOSQUITO LARVICIDAL POTENTIALITY OF Holoptelea integrifolia - SINGHA, S.; CHANDRA, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Japanese encephalitis (JE) which was previously known as Japanese B encephalitis, is caused by the Japanese encephalitis virus. Plant produced the photochemical mainly for their own defense mechanism is experimentally used to control varieties of insect pests or vectors. Crude extract (0.1%, 0.2%, 0.3%, 0.4% and 0.5%) of leaves of Holoptelea integrifolia when applied on third instars mosquito larvae in successive seasons i.e. Summer, Rainy and Winter, caused 100 percent mortality at 0.5% concentration in summer after 72 h of exposure. In Winter, also a 100 percent mortality of the third instars of Cx. vishnui group larvae were noticed after 48 h of exposure at 0.5% concentration. Out of three predominant seasons in West Bengal, variation in the mortality of Cx. vishnui group larvae by crude extract of H. integrifolia leaf are well established and mortality increases with higher extract concentration and time of exposure. Highest mortality was noted in Rainy season followed by Summer and Winter.